Po co literaturze dawnej współczesna teoria? - Bohuszewicz, Paweł (Litteraria Copernicana, 2008)
The article consists of three chapters. In the first one – titled A philological-autonomous Paradigm in Polish History of Old Literature – I discuss a state of studies on polish old literature, considering it belongs to so-called philological-autonomous paradigm in the theory of literature. This paradigm treats the theory of literature as a separate branch of science that has its own subject and its own method of research but that method should be a traditionally and generally taken philology. In the second chapter – that is titled The Swallows of New – I concentrate in research texts, which in various ways are against the earlier discussed paradigm, therefore I define them as „serialism” and „continuationism”. In last chapter I draw conclusions from consideration in the previous chapters contained and I give a general answer to the question put in the title of this article.